Analisis Hubungan Work Life Balance dan Kinerja Pegawai di Badan Pendapatan Daerah - Kusuma, Angga Aria (Universitas Mitra Indonesia, 2024)
Employee performance does not only include achieving individual targets but also influences the effectiveness and efficiency of achieving organizational goals. This research aims to analyze the influence of work life balance on employee performance. The object of the research was the ASN at the Regional Revenue Agency of Serang Regency. The population and sample size was determined as 56 respondents using total sampling technique. Data analysis uses a simple linear regression approach processed with the SPSS program. The research results show that there is a significant influence of work life balance on employee performance, as indicated by an R Square value of 15.2%. Keywords : Regional Revenue Agency, Employee Performance, Work life balance